Environmental Impact of Ophthalmology and Related Action Plan: Sustainability Inside and Outside of the Operating Room (Canadian Eye Care Today, 2023)
Climate change, global warming, or “global weirding” as some experts call it, is now undeniable. Extreme weather events such as flash floods, fires and hurricanes are increasing in both frequency and intensity. These changes are directly influenced by a changing climate as a by-product of greenhouse gas emissions, principally but not exclusively carbon dioxide (CO2) and methane (CH4).